ISSUES OF TRAINING YOUNG LEADERS AND INSTILLING LEADERSHIP QUALITIES IN THE CONTEXT OF UZBEKISTAN: NATIONAL MODEL, POLITICAL CULTURE, AND INNOVATIVE APPROACHES. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the key aspects of training young leaders and instilling leadership qualities in the context of Uzbekistan. It highlights the importance of forming a new generation of competent and responsible leaders who are capable of meeting the demands of a rapidly changing society. The study explores the national model of leadership development, the role of political culture in shaping leadership behavior, and the implementation of innovative approaches in the educational and administrative systems. Special attention is given to the integration of traditional values with modern leadership principles. The research also provides insights into the current strategies used in Uzbekistan to foster youth leadership and improve their decision-making, communication, and strategic thinking skills. Overall, the article aims to contribute to the development of an effective national framework for empowering young leaders in the country.